Immune response to chemically modified proteome - Bhat, Shweta; Mary, Sheon; Banarjee, Reema; Giri, Ashok P.; Kulkarni, Mahesh J. (Proteomics Clinical Applications, 2014)
Both enzymatic and nonenzymatic PTMs of proteins involve chemical modifications. Some of these modifications are prerequisite for the normal functioning of cell, while other chemical modifications render the proteins as neo-self antigens, which are recognized as non-self leading to aberrant cellular and humoral immune responses. However, these modifications could be a secondary effect of autoimmune diseases, as in the case of type I diabetes, hyperglycemia leads to protein glycation. The enigma of chemical modifications and immune response is akin to the chick-and-egg paradox. Nevertheless, chemical modifications regulate immune response. In some of the well-known autoimmune diseases such as rheumatoid arthritis, systemic lupus erythematosus, and multiple sclerosis, chemically modified proteins act as autoantigens forming immune complexes. In some instances, chemical modifications are also involved in regulating immune response during pathogen infection. Further, the usefulness of proteomic analysis of immune complexes is briefly discussed.
Keywords: Autoantibody; Autoimmune diseases; Immune complex; Immunoproteomics; PTMs